2017
DOI: 10.1371/journal.pone.0187274
|View full text |Cite
|
Sign up to set email alerts
|

Global transcriptome profile reveals abundance of DNA damage response and repair genes in individuals from high level natural radiation areas of Kerala coast

Abstract: The high level natural radiation areas (HLNRA) of Kerala coast in south west India is unique for its wide variation in the background radiation dose (<1.0mGy to 45mGy/year) and vast population size. Several biological studies conducted in this area did not reveal any adverse effects of chronic low dose and low dose rate radiation on human population. In the present study, global transcriptome analysis was carried out in peripheral blood mono-nuclear cells of 36 individuals belonging to different background dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 70 publications
(96 reference statements)
1
10
0
Order By: Relevance
“…Similarly, in another study, P53 expression in radiation workers was significantly higher than that of the control group and showed that low and chronic doses of ionizing radiation play an important role in increasing the expression of P53 amongst radiation workers [21]. In several studies, the role of P53 in radio-adaptive response was reported [22][23][24]. Regarding the results of our research and previous studies, P53 expression is important for the safety of workers exposed to genotoxic agents such as ionizing radiation and anesthetic gases.…”
Section: Discussionmentioning
confidence: 81%
“…Similarly, in another study, P53 expression in radiation workers was significantly higher than that of the control group and showed that low and chronic doses of ionizing radiation play an important role in increasing the expression of P53 amongst radiation workers [21]. In several studies, the role of P53 in radio-adaptive response was reported [22][23][24]. Regarding the results of our research and previous studies, P53 expression is important for the safety of workers exposed to genotoxic agents such as ionizing radiation and anesthetic gases.…”
Section: Discussionmentioning
confidence: 81%
“…DDR induced by genotoxic stress including IR lead to alteration of gene expression profile in human cells [ 17 , 18 ]. Several studies have demonstrated early and late responses of miRNA expression of several genes involved in various cellular and molecular processes in human cells in response to IR.…”
Section: Discussionmentioning
confidence: 99%
“…Both homologous recombination repair (HRR) or non-homologous end-joining (NHEJ) repair mechanisms are activated due to LDIR exposure in cell lines in culture, but NHEJ is more active in resting PBMCs. Recent studies from high level natural background radiation areas have shown efficient repair of DSBs and activation of DDR, NHEJ, HR and other signaling pathways in PBMCs at low lose radiation exposed human population [ 16 , 17 ]. Evidences of the involvement DDR and BER repair pathway in human PBMCs have also been found at DNA damage, repair and mRNA expression level [ 18 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that the cited studies focused on different immune parameters their conclusions were quite convergent, showing increased activity in the adaptive immune response and the presence of pro-inflammatory factors. A recent study on gene expression profiles of PBMCs from inhabitants of the high level background radioactivity area in Kerala, India found that immune response pathways were among the radiation-affected over-represented pathways ( Jain and Das, 2017 ).…”
Section: Human Biomonitoring and Epidemiological Data On Low Dose Radiation-induced Immunological Changesmentioning
confidence: 99%